The Mechanisms of Canal Cultural Heritage Influence on the Evolution and Sustainability of Regional Martial Arts Traditions: A Case Study of Cangzhou Martial Arts in the Grand Canal Context - Miao, Feng; Sun, Minghua (Journal of Theory and Practice of Social Science, 2024)
This study aims to explore the mechanism of the influence of the Grand Canal cultural heritage on the evolution and sustainability of traditional martial arts in Cangzhou. As one of the most important ancient water conservancy projects and transportation arteries in China, the Grand Canal carries profound historical culture and humanistic spirit, which plays an important role in shaping and inheriting local culture. Cangzhou, as one of the important cities along the Grand Canal, has a long history of martial arts culture, which has been passed down from generation to generation and integrated with a large number of local characteristics and historical traditions. However, with the changes of times and social development, Cangzhou martial arts faces new challenges and opportunities. How to inherit and develop in modern society, maintain its uniqueness and vitality become urgent problems. Through in-depth analysis of the relationship between the Grand Canal cultural heritage and Cangzhou martial arts tradition, this study found that the influence of the Grand Canal on Cangzhou martial arts mainly manifests in several aspects. Firstly, the construction and operation of the Grand Canal promoted population mobility and cultural exchange, brought collisions and fusion of martial arts traditions from different regions, and enriched the skills and styles of martial arts. Secondly, the economic and trade activities of the Grand Canal provided a soil and resource support for the development of Cangzhou martial arts, enabling it to be inherited and strengthened. At the same time, the influence of the Grand Canal culture also subtly penetrated into the spiritual connotation and aesthetic taste of Cangzhou martial arts, affecting the identification and pursuit of martial arts practitioners and enthusiasts. In exploring the influence process of the Grand Canal cultural heritage on the sustainability of Cangzhou martial arts, this study emphasizes the importance of updating and innovating cultural traditions. Traditional culture needs to radiate new vitality in contemporary society, which requires not only retaining the essence of tradition but also constantly absorbing external cultural elements and innovative ideas, expanding development space, and achieving the organic combination of tradition and modernity. Therefore, the Grand Canal cultural heritage is not only the historical source of Cangzhou martial arts development but also the inspiration and support for its future development. Through in-depth research on the interactive relationship between the Grand Canal cultural heritage and Cangzhou martial arts tradition, we can better promote the inheritance and innovation of martial arts culture and provide useful references and inspirations for the sustainable development of local culture.